Cesium nD_{J}+6S_{1/2} Rydberg molecules and their permanent electric dipole moments - Suying Bai; Xiaoxuan Han; Jingxu Bai; Yuechun Jiao; Jianming Zhao; Suotang Jia; Georg Raithel (Physical Review Research, 2020)
Cs_{2} Rydberg-ground molecules consisting of a Rydberg, nD_{J} (33≤n≤39), and a ground-state atom, 6S_{1/2} (F=3 or 4), are investigated by photo-association spectroscopy in a cold atomic gas. We observe vibrational spectra that correspond to triplet ^{T}Σ and mixed ^{S,T}Σ molecular states. We establish scaling laws for the energies of the lowest vibrational states vs principal quantum number and obtain zero-energy singlet and triplet s-wave scattering lengths from experimental data and a Fermi model. Line broadening in electric fields reveals the permanent molecular electric-dipole moments. Measured values agree well with calculations, which also reveal that the dipole moments are negative. The negative sign reflects a deficiency of Rydberg-electron density near the ground-state perturber, which is caused by electronic configuration mixing. The mixing leads to destructive wave function interference near the perturber. This case differs from previous reports of positive dipole moments, where the interference near the perturber is constructive.